Suggested: differentiate y=(2x+1)^5(x^3-x+1)^4 - differentiate (2x+1)^5(x^3-x+1)^4 - (2x-1)(x-3)=(x+5)(x-1) - 3(x-3)=5(2x-1) solve - check whether the following are quadratic equation (x-3)(2x+1)=x(x+5) - 5x-2/1+2x+3x^2 - solve for x 2(2x-1/x+3)-3x+3/2x-1)=5 - x=1/2-√3 find the value of x^3-2x^2-7x+5 - 5(x-1)+2x+3)+6=0 - x-5/2x-3/5=1/2 class 8 - solve the equation (2x-3)(6x-1)(3x-2)(x-2)-5=0 - 2x+y=-4 3y=5 x-1 - 2x-3/5x+3/4=4x+1/7 - the constant term in the expansion of (2x+(1)/(x^(7))+3x^(2))^(5) is - (2x+1)^5(x^3 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.